Homologs of LEAFY and UNUSUAL FLORAL ORGANS Promote the Transition From Inflorescence to Floral Meristem Identity in the Cymose Aquilegia coerulea - Sharma, Bharti; Meaders, Clara; Wolfe, Damien; Holappa, Lynn; Walcher-Chevillet, Cristina; Kramer, Elena M. (Frontiers in Plant Science, 2019)
Homologs of the transcription factor LEAFY (LFY) and the F-box family member UNUSUAL FLORAL ORGANS (UFO) have been found to promote floral meristem identity across diverse dicot model systems. The lower eudicot model Aquilegia produces cymose inflorescences that are independently evolved from the well-studied cymose models Petunia and tomato. We have previously characterized the expression pattern of the Aquilegia homolog AqLFY but in the current study, we add expression data on the two UFO homologs, AqUFO1 and 2, and conduct virus-induced gene silencing of all the loci. Down-regulation of AqLFY or AqUFO1 and 2 does not eliminate floral meristem identity but, instead, causes the transition from inflorescence to floral identity to become gradual rather than discrete. Inflorescences in down-regulated plants generate several nodes of bract/sepal chimeras and, once floral development does commence, flowers initiate several whorls of sepals before finally producing the wildtype floral whorls. In addition, silencing of AqUFO1/2 appears to specifically impact petal identity and/or the initiation of petal and stamen whorls. In general, however, there is no evidence for an essential role of AqLFY or AqUFO1/2 in transcriptional activation of the B or C gene homologs. These findings highlight differences between deeply divergent dicot lineages in the functional conservation of the floral meristem identity program.